Kecanduan Media Sosial dalam Perspektif Psikologis: Peran Kesepian dan Perilaku Narsistik - Handoyo, Ferbian Kembar; Riza, Wina Lova; Aisha, Dinda (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the influence of loneliness and narcissistic behavior on social media addiction among emerging adults in Karawang. The method used in this study is quantitative, with a causal research design. The population in this study consists of emerging adults residing in Karawang. The sample in this study consisted of 356 respondents, calculated based on Issac Michael's formula and using convenience sampling techniques. The measurement tools used in this study were psychological scales: the UCLA Loneliness Scale v3 for loneliness, the Narcissistic Personality Inventory 16 for narcissistic behavior, and the Social Media Disorder Scale for social media addiction. Based on the results of the study, there was no significant simultaneous effect between the variables of loneliness and narcissistic behavior on social media addiction. However, partially, only the narcissistic behavior variable showed a significant effect on social media addiction, while the loneliness variable did not have a significant effect.